DETERMINATION OF THE HEAT TRANSFER COEFFICIENT DURING ANNULAR FLOW CONDENSATION IN SMOOTH HORIZONTAL TUBES - Agra, Ozden; Teke, Ismail (TURKISH SOC THERMAL SCIENCES TECHNOLOGY, 2012)
In this study, a model describing the relationship between pressure drop and heat transfer coefficients was developed to calculate the heat transfer coefficient under two-phase annular flow conditions. According to these conditions, the single phase liquid flow with temperature distribution which is equivalent to velocity and temperature distributions in the liquid film was determined and the heat transfer coefficient during condensation was calculated from equations provided for the single-phase liquid. The results of the new analytical model were compared with the heat transfer coefficient obtained from experimental study. In this study, the refrigerant (R600a) was circulated inside a smooth horizontal tube with an inner diameter 4 mm and the experimental results were found to be consistent with the mentioned correlations within a range of +/- 20%. Consequently, to validate the model, the heat transfer coefficient data in the literature were compared with the heat transfer coefficient values of the analytical model study, under the same conditions. A deviation of +/- 25% was found as a result of the comparison.
Keywords: Hydrocarbon; Pure refrigerant; Condensation; Heat transfer coefficient; MODEL; Thermodynamics; Engineering